Gérard Bessette (1920-2005): a monstre sacré in French Canadian Literature - Steven Urquhart (Studies in 20th & 21st Century Literature, 2011)
This article examines Gérard Bessette’s relative marginalization in French Canadian literature by means of rereading his first novel, La Bagarre (1958) in terms of its monstrous aesthetic and its rapport with subsequent novels, notably Le Semestre (1979). Bessette’s first novel allows us not only to understand the deviant nature of his aesthetic and its evolution, but also how it relates to his individualistic and transgressive position with the French Canadian literary institution in which he embodies a monstre sacré, an author and a character of sorts, who is at once revered and cursed.
Keywords: Gérard Bessette; French Canadian literature; marginalization; novel; aesthetic; monstre sacré